Talent selection in 3 × 3 basketball: role of anthropometrics, maturation, and motor performance - Schmitz, Tim Luca; Fleddermann, Marie-Therese; Zentgraf, Karen (Frontiers in Sports and Active Living, 2024)
3x3 basketball is becoming more and more professionalized, which is leading to a growing interest in talent development and talent selection. Different studies have demonstrated relevant factors in the talent selection process of 5v5 basketball but not in 3x3 basketball. Therefore, this study investigated the main predictors in the talent selection process in 3x3 basketball athletes.A total of 192 athletes (Mage = 16,11 ± 0,45 years; n = 85 were female) 3x3 basketball athletes were assessed for various anthropometric and motor performance variables as well as maturity status. All assessments were carried out during selection camps for the German "under 17" youth national team. Binomial logistic regression was conducted to determine which variables predicted selection (either 'selected', n = 30 female and n = 34 male, or 'non-selected', n = 55 female and n = 73 male).The regression model was statistically significant in female athletes (χ² (3) = 26.86, p < .001). It explains 37.9% (Nagelkerke´s R 2 ) of the variance in selection status and suggests that the general motor-performance component (p < .001) and the anthropometric-and maturation-related component (p = .004) seem to be relevant for being selected. In male athletes the binomial logistic regression model was also statistically significant (χ² (3) = 11.38, p = .010) with explaining 14.2% (Nagelkerke´s R 2 ) of the variance in selection status but only the anthropometric-and maturationrelated component (p = .004) predict selection.Anthropometric conditions (such as body height, body weight, and wingspan) and the maturity status are particularly important in talent selection in 3x3 basketball for both sexes. Regarding motorperformance variables, we found a predictive value for talent selection only in females (without sprinting), but not in males which means that more 'athletic' female athletes seem to be favoured in talent selection. The results suggest that the talent selection process might be biased by maturation status even in middle adolescence. Therefore, coaches who decide on athletes' selection should be aware of the temporal advantages induced by earlier maturation when evaluating talented athletes and should consider strategies such as bio-banding to evaluate the real and potential value of talented athletes.